The Analysis of Ambient Air Quality with Sulfur Dioxide (SO2) and Carbon Monoxide (CO) Parameters at the Final Disposal Site (TPA) of Air Dingin, Padang City - Andriani, Windi; Muhelni, Leila; Edinov, Sanny; Mukhtar, Dertha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Air Dingin Landfill (TPA) in Padang City is a major waste disposal site, with open burning and waste decomposition activities producing hazardous gas emissions. This study aims to analyze the concentrations of sulfur dioxide (SO₂) and carbon monoxide (CO) as air pollution parameters around the landfill. Sampling was conducted in the active area of the Air Dingin Landfill on May 19, 2025. Laboratory analysis compared the concentrations of SO₂ and CO to ambient air quality standards established by Government Regulation No. 22 of 2021. The results showed that the SO₂ concentration was 173 µg/m³ and CO was 4,170 µg/m³, both exceeding the established standards. These findings indicate the need for emission management and combustion activity control to minimize the impact of air pollution.